THE MEDIATING ROLE OF SELF-EFFICACY ON THE EFFECT OF PEER GROUP ON SELF-REGULATED LEARNING - Nurrahmatullah, Muh. Fiqri; Waspada, Ikaputera; Mulyani, Heni (Universitas Muhammadiyah Surakarta, 2024)
This study aims to determine the role of self-efficacy in mediating peer groups on self-regulated learning. The theory used is Social Cognitive Theory of Self-regulation. The population amounted to 358 students so that the sampling technique amounted to 189 accounting education students of Universitas Pendidikan Indonesia. Data collection using a questionnaire. Data analysis techniques using Structural Equation Modeling (SEM) with Smart PLS 3 because Smart PLS 3 can measure a small population. The results showed that peer group has a positive and significant influence on self-regulated learning, peer group has a positive and significant influence on self-efficacy, self-efficacy has a positive and insignificant effect on self-regulated learning, and self efficacy does not mediate the effect of peer group on self-regulated learning. The benefit of these findings for society is the creation of individuals who are more independent, confident, and able to regulate their own learning. Students who have good self-regulated learning skills and high self-efficacy tend to be more able to face academic and professional challenges more effectively.